Does corporate diversification destroy value? further evidence from mergers and acquisitions in Singapore. - Goh, Tze Ying. (2008)
We found that mergers and acquisitions in Singapore generally create value for the firms. High managerial ownership coupled with diversification strategy help to generate a higher return for the firm. However in the long run, there is no significant change of firm value for firms that undertake mergers and acquisitions.